Principal's Strategy to Improve Education Quality - Fatimah Azzahra Lubis; Makmur Syukri (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This research examines the principal's strategy in improving the quality of education in schools. The focus of this research is the identification and analysis of effective strategies used by school principals in achieving these goals. This research uses a qualitative approach with case study methods in several leading schools. Data was collected through in-depth interviews, observation and document analysis. The research results show that school principals who are successful in improving the quality of education generally implement several main strategies. First, they develop a clear vision and mission and encourage the active participation of all school members in achieving it. Second, they implement school-based management by involving teachers, staff, students and parents in decision making. Third, they focus on teacher professional development through training, workshops and collaboration between teachers to improve the quality of teaching. Fourth, the school principal ensures a conducive learning environment by providing adequate facilities and resources. Fifth, they carry out regular evaluation and monitoring of the teaching and learning process and student performance. The results of this research provide insight for educational practitioners and policy makers in efforts to improve the quality of education in schools. It is hoped that these strategies can become a model for other school principals in carrying out their duties to achieve quality education.